GEOENVIRONMENTAL UNITS IN HIDROGRAPHIC BASIN OF THE ITU RIVER - WEST OF THE STATE OF RIO GRANDE DO SUL, BRASIL - Trentin, Romario; Robaina, Luís Eduardo de Souza (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2012)
Environmental studies, seeking knowledge of resources and the weaknesses do part of the work of Environmental Geology Laboratory (LAGEOLAM – UFSM) during the past 15 years. The west-southwest of Rio Grande do Sul represents an area of great environmental degradation with accelerated processes of erosion, gullies, and sands process. This paper analyzes and maps geo-environmental units in Itu River basin, using a mapping scale of 1:50,000. The components represent a geo-environmental interaction between the characteristics of the physical environment (topography, geology, drainage, soils, precipitation, surface features) and the use and occupation of land. The work defined 9 units as those with homogeneous characteristics from dynamic surface processes, which are: unity of recent deposits, sandstone hills, hills of volcanic rocks, flat tops, sandstone buttles of the sandstones, buttles of volcanic rock, steep topography, urban use, processes of sands. This map serves as a tool in regional development projects and resource management.